1999
DOI: 10.1046/j.1365-2036.1999.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of S‐0509, a novel CCKB/gastrin receptor antagonist, on acid secretion and experimental duodenal ulcers in rats

Abstract: Background: S‐0509, 2‐[(tert‐butoxycarbonylmethyl) [(m‐(carboxy‐phenyl)‐ureidomethyl‐carbonyl]] aminobenzo phenone, was developed as a potent and selective CCKB/gastrin receptor antagonist that does not affect the central nervous system. Methods: We evaluated the effects of S‐0509 on gastric acid secretion and duodenal ulcerogenic and healing responses in rats comparing it with L‐365,260, another CCKB/gastrin receptor antagonist. Results: S‐0509 (0.1~10 mg/kg, i.d.) was able to dose‐dependently decrease basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In contrast, Takeuchi et al . recently reported that S‐0509 had no effect on carbachol‐stimulated gastric acid secretion in anesthetized rats 13 . Consequently, we examined the effectiveness of S‐0509 on gastric acid secretion in dogs as a selective gastrin antagonist.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, Takeuchi et al . recently reported that S‐0509 had no effect on carbachol‐stimulated gastric acid secretion in anesthetized rats 13 . Consequently, we examined the effectiveness of S‐0509 on gastric acid secretion in dogs as a selective gastrin antagonist.…”
Section: Introductionmentioning
confidence: 98%
“… 7 In terms of pharmacological studies, it has been shown in animal studies that selective cholecystokinin‐B/gastrin receptor antagonists, such as YM022, YF476 or S‐0509, extensively inhibit gastric acid secretion in response to peptone or beer. 8–13 To our knowledge, however, no data have been reported detailing the effects of the combination of peptone and beer, which may result in a much stronger stimulation of acid secretion.…”
Section: Introductionmentioning
confidence: 98%
“…L‐365260 has a poor bioavailability, a very short half‐life, and is ineffective in inhibiting basal acid secretion. Compared with the H 2 RA famotidine, YM‐022 was equally effective in rats in preventing indomethacin‐induced ulcers, but it is no longer clinically developed owing to the development of tachyphylaxis [21]. Agents currently in development include Z‐360 and itriglumide.…”
Section: Preventing Stimulation Of the Parietal Cellmentioning
confidence: 99%